Dampak pekerja sosial, pembangunan kesejahteraan sosial dan desentralisasi pembangunan kesejahteraan sosial terhadap pendapatan kelompok usaha bersama di Kecamatan Kota Selatan Kota Gorontalo, 2009 - ABDURAF, Rasam ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Research on the impact of social empowerment direct assistance to the income of joint ventures in South City district of Gorontalo city in 2009 was aimed to analyze the influence of social workers, social welfare development and decentralization of social welfare development of the income of joint ventures and analyze the level of income together within the group, before and after receive direct support both in economically productive social empowerment. The data required in this study are primary and secondary data. The primary data obtained through interviews with members of business groups with direct assistance beneficiaries of productive economic empowerment of 30 people by using questionnaires that have been provided. Secondary data collected from several sources ie offices / agencies. The analytical tool used to analyze the influence of social workers, social welfare development and decentralization of social welfare development of joint business group revenues were multiple linear regression. Dependent variable is the income group of joint ventures, while independent variables are social workers, social welfare development and decentralization of social welfare. Then analyzed with the method of Ordinary Least Square (OLS). To analyze the level of income together with business groups before and after receiving direct support social empowerment social programs in economically productive use two different test analysis tools on average, by comparing income with business groups before and after receiving direct support social empowerment. From the analysis the influence of social workers, social welfare development and decentralization of social welfare development of the income of a collaborative effort with α= 0.05 obtained R ²= 0.502, respectively with: social worker= 1.399, social welfare development= 2, 597 and decentralization of social welfare development= 0.463 and F table= 8.741. Social welfare development partially significant (significantly) to group revenue joint venture, a social worker and the decentralization of social welfare development did not significantly affect the income of a partnership, decentralization of social workers and welfare development and decentralization of social welfare development significantly affect on income business group. Revenue per month together with the business group after receiving assistance and significantly greater degree of confidence of 95 percent compared to prior receiving direct support social empowerment productive economic empowerment programs.